Fear and loathing - Sardar, Ziauddin; Yassin-Kassab, Robin (Critical Muslim ;, 2012)
In the third issue of Critical Muslim : AbdelWahab El-Affendi on Islamophobia and Orientalism in the age of liberal paranoia, Arun Kundnani on English Defense League and the rise of the far right in Europe, Vinay Lal on Hindus who love Hitler, Gordon Steffey on Christian fundamentalism, Fanar Haddad on the sectarian schisms in the Arab world, Gary McFarlane on Tottenham Riots, Farouk Peru on self loathing Muslims, Claire Chambers on 'Four Lions', Peter Clark on Bernard Lewis and Peter Moray on Irshad Manji. Plus a short story by Suhel Ahmed, six poems by Stéphane Chaumet, Anita Sethi's dangerous bus ride through Iran, Ten Top Techs for Muslim and Ziauddin Sardar on his pet hate : the beards of Islam.